• ### How to find the slope of a line with decimals?

slope = (12 - 10)/(3.05 - 2.78) = 2/0.27 = 7.41
slope = (12 - 10)/(3.05 - 2.78) = 2/0.27 = 7.41
8 answers · Mathematics · 6 years ago
• ### How to factor 12b^2-192?

12b^2-192=12(b^2-16)=12(b±4)(b-4) 1.
12b^2-192=12(b^2-16)=12(b±4)(b-4) 1.
5 answers · Mathematics · 6 years ago
• ### Hard essay question need help!!?

Megan got the correct coefficients but got the sign of the constants interchanged. The correct factors are (9x + 1)(3x - 6). Jacob also applied the FOIL incorrectly. He should have gotten 27x^2 + 51x - 6.
Megan got the correct coefficients but got the sign of the constants interchanged. The correct factors are (9x + 1)(3x - 6). Jacob also applied the FOIL incorrectly. He should have gotten 27x^2 + 51x - 6.
4 answers · Mathematics · 8 years ago
• ### Very hard maths question?

let 2n = the first of the even numbers The second one = 2n + 2 (2n + 2)² – (2n)² = (4n² + 8n + 4) – 4n² .......................... = 8n + 4 .......................... = 2(4n + 2) .......................... = 2(2n + 2n + 2) .......................... = 2[(2n) + (2n + 2)]
let 2n = the first of the even numbers The second one = 2n + 2 (2n + 2)² – (2n)² = (4n² + 8n + 4) – 4n² .......................... = 8n + 4 .......................... = 2(4n + 2) .......................... = 2(2n + 2n + 2) .......................... = 2[(2n) + (2n + 2)]
5 answers · Mathematics · 8 years ago
• ### 5/2u-1/2=-4/5u-6 What does "u" equal?

5/2u-1/2=-4/5u-6 Multiply by 10u 25 - 5u =- 8 -60u 33 = -55u u = 22/(-55) = -2/5
5/2u-1/2=-4/5u-6 Multiply by 10u 25 - 5u =- 8 -60u 33 = -55u u = 22/(-55) = -2/5
7 answers · Mathematics · 8 years ago
• ### Pls help with this set theory?

Best answer: n(U) = 209 n(G) = 100 n(S) = 84 n(H) = 92 n(G∪S) = 39 n(G∪H) = 32 n(S∪H) = 32 n(G∪H∪S) = 209 – 13 = 196 n(G∪H∪S) = n(G) + n(S) + n(H) - n(G∪S) - n(G∪H - n(S∪H) + n(G∩H∩S) 196 = 100 + 84 + 92 - 39 - 32 - 32 + n(G∩H∩S) 196 = 173+ n(G∩H∩S) n(G∩H∩S) = 196 - 172 = 24 A. How many drink all... show more
Best answer: n(U) = 209 n(G) = 100 n(S) = 84 n(H) = 92 n(G∪S) = 39 n(G∪H) = 32 n(S∪H) = 32 n(G∪H∪S) = 209 – 13 = 196 n(G∪H∪S) = n(G) + n(S) + n(H) - n(G∪S) - n(G∪H - n(S∪H) + n(G∩H∩S) 196 = 100 + 84 + 92 - 39 - 32 - 32 + n(G∩H∩S) 196 = 173+ n(G∩H∩S) n(G∩H∩S) = 196 - 172 = 24 A. How many drink all 3 n(G∩H∩S) = 24 B. How many drink star only? star only = n(S) - n(G∪S) - n(S∪H) + n(G∩H∩S) = 84 - 39 - 32 + 24= 37 C. How many drink guilder only? guilder only = n(G) - n(G∪S) - n(S∪H) + n(G∩H∩S) = 100 - 39 - 32 + 24= 53 D. How many drink harp only? harp only = n(H) - n(G∪H) - n(S∪H) + n(G∩H∩S) = 92 - 32 - 32 + 24= 52
1 answer · Mathematics · 8 years ago
• ### How to do this A math sum?

p = (1 + 1 / √3)/(1 – 1 / √3) Multiply both numerator and denominator by √3 p = (√3 + 1)/(√3 – 1) rationalize multiplying both numerator and denominator by (√3 + 1) p = (√3 + 1)(√3 + 1)/(√3 – 1)(√3 + 1) p = (3 + 2√3 + 1)/(3 – 1) p = (4 + 2√3)/2 p = 2 + √3 p – 1/p = 2 + √3 - 1/(2 + √3) p – 1/p = [(2 + √3)² - 1]/(2 + √3) p – 1/p = [4 – 4√3 + 3 -... show more
p = (1 + 1 / √3)/(1 – 1 / √3) Multiply both numerator and denominator by √3 p = (√3 + 1)/(√3 – 1) rationalize multiplying both numerator and denominator by (√3 + 1) p = (√3 + 1)(√3 + 1)/(√3 – 1)(√3 + 1) p = (3 + 2√3 + 1)/(3 – 1) p = (4 + 2√3)/2 p = 2 + √3 p – 1/p = 2 + √3 - 1/(2 + √3) p – 1/p = [(2 + √3)² - 1]/(2 + √3) p – 1/p = [4 – 4√3 + 3 - 1]/(2 + √3) p – 1/p = (6 – 4√3)/(2 + √3) p – 1/p = (6 – 4√3)(2 – √3)/(2 + √3)(2 – √3) p – 1/p = (12 – 14√3 + 12)/(4 – 3) p – 1/p = (24 – 14√3)/1 p – 1/p = 24 – 14√3
4 answers · Mathematics · 8 years ago
• ### How to expand : (2+√3)(1+√3) ...give your answer in the form a+b√3, where a and b are integers?

(2 + √3)(1 + √3) = (2)(1 + √3) + (√3)(1 + √3) .......................... = 2 + 2√3 + √3 + 3 .......................... = 5 + 3√3 a = 5, b = 3
(2 + √3)(1 + √3) = (2)(1 + √3) + (√3)(1 + √3) .......................... = 2 + 2√3 + √3 + 3 .......................... = 5 + 3√3 a = 5, b = 3
7 answers · Mathematics · 8 years ago
• ### Expand (1+4x)^4in accending powers of x?

Best answer: (1 + 4x)⁴ = 1⁴ + 4(1)³(4x) + 6(1)²(4x)² + 4(1)(4x)³ + (4x)⁴ (1 + 4x)⁴ = 1 + 16x + 96x² + 256x³ + 246x⁴
Best answer: (1 + 4x)⁴ = 1⁴ + 4(1)³(4x) + 6(1)²(4x)² + 4(1)(4x)³ + (4x)⁴ (1 + 4x)⁴ = 1 + 16x + 96x² + 256x³ + 246x⁴
5 answers · Mathematics · 8 years ago
• ### Can you help match these math words with their definition?

proportion is an equation that states that two ratios are equivalent conversion factor is a fraction whose numerator and denominator represent the same quantity but use different units; the fraction is equal to 1 because the numerator and denominator are equal equivalent ratios are ratios that name the same comparison
proportion is an equation that states that two ratios are equivalent conversion factor is a fraction whose numerator and denominator represent the same quantity but use different units; the fraction is equal to 1 because the numerator and denominator are equal equivalent ratios are ratios that name the same comparison
4 answers · Mathematics · 8 years ago
• ### Factor f(x) = x3 – 2x2 - 9x + 18 completely.?

Best answer: Factor f(x) = x³ – 2x² – 9x + 18 x³ – 2x² – 9x + 18 = (x³ – 2x²) – (9x – 18) x³ – 2x² – 9x + 18 = x²(x – 2) – 9(x – 2) x³ – 2x² – 9x + 18 = (x – 2)(x² – 9) x³ – 2x² – 9x + 18 = (x – 2)(x + 3)(x – 3)
Best answer: Factor f(x) = x³ – 2x² – 9x + 18 x³ – 2x² – 9x + 18 = (x³ – 2x²) – (9x – 18) x³ – 2x² – 9x + 18 = x²(x – 2) – 9(x – 2) x³ – 2x² – 9x + 18 = (x – 2)(x² – 9) x³ – 2x² – 9x + 18 = (x – 2)(x + 3)(x – 3)
3 answers · Mathematics · 8 years ago
• ### Rational Functions Problem?

r(x) = (6x + 3)/(x² + 1), s(x) = (x² + 4)/(4x – 1) (r – s)(x) = (6x + 3)/(x² + 1) – (x² + 4)/(4x – 1) .............. = (6x + 3)(4x – 1) – (x² + 1)(x² + 4)/((4x – 1)(x² + 1)) .............. = (24x² + 6x – 3) – (x⁴ + 5x² + 4)/(4x³ – x² + 4x – 1) .............. = (– x⁴ + 19x² + 6x – 7)/(4x³ – x² + 4x – 1) (r - s)(x) = f(x)/g(x where f(x) =... show more
r(x) = (6x + 3)/(x² + 1), s(x) = (x² + 4)/(4x – 1) (r – s)(x) = (6x + 3)/(x² + 1) – (x² + 4)/(4x – 1) .............. = (6x + 3)(4x – 1) – (x² + 1)(x² + 4)/((4x – 1)(x² + 1)) .............. = (24x² + 6x – 3) – (x⁴ + 5x² + 4)/(4x³ – x² + 4x – 1) .............. = (– x⁴ + 19x² + 6x – 7)/(4x³ – x² + 4x – 1) (r - s)(x) = f(x)/g(x where f(x) = – x⁴ + 19x² + 6x – 7 g(x) = 4x³ – x² + 4x – 1
1 answer · Mathematics · 8 years ago
• ### Maths help needed....?

Best answer: antiderivative(5x² + 4x – 6) = (5/3)x³ + (4/2)x² – 6x + c = 5x³/3 + 2x² – 6x + c
Best answer: antiderivative(5x² + 4x – 6) = (5/3)x³ + (4/2)x² – 6x + c = 5x³/3 + 2x² – 6x + c
1 answer · Mathematics · 8 years ago
• ### Pls answer ths simple question maths?

Best answer: Area ABC = ½(x)(BC) Area ABD = ½(x)(BD) Area ABD = ½(Area ABC) Area ABC = 2(Area ABD) ½(x)(BC) = 2(½)(x)(BD) BC = 2BD (y + z) = 2(y) z = y w² = x² + (y + z)² = x² + (y + y)² = x² + 4y² = (x² + y²) + 3y² (AB) = x² + y² w² = (AB)² + 3y² (AB)² = w² – 3y² AB = √(w² – 3y²) Therefore the correct answer is (4)
Best answer: Area ABC = ½(x)(BC) Area ABD = ½(x)(BD) Area ABD = ½(Area ABC) Area ABC = 2(Area ABD) ½(x)(BC) = 2(½)(x)(BD) BC = 2BD (y + z) = 2(y) z = y w² = x² + (y + z)² = x² + (y + y)² = x² + 4y² = (x² + y²) + 3y² (AB) = x² + y² w² = (AB)² + 3y² (AB)² = w² – 3y² AB = √(w² – 3y²) Therefore the correct answer is (4)
2 answers · Mathematics · 8 years ago
• ### Is there a Math Rule that states if 2 of a triangle's angles are congruent, the third angles will be congruent?

Yes. Because of the rule that the sum of the angles of a triangle is always 180º. Let the angles of the a triangle be α₁, β₁, γ₁ and that of the second triangle be α₂, β₂, γ₂. Then: α₁ + β₁ + γ₁ = 180º α₂ + β₂ + γ₂ = 180º Since the two angles are congruent α₁ = α₂ = α β₁ = β₂ = β α + β + γ₁ = 180º α + β + γ₂ = 180º γ₁ = 180º – (α +... show more
Yes. Because of the rule that the sum of the angles of a triangle is always 180º. Let the angles of the a triangle be α₁, β₁, γ₁ and that of the second triangle be α₂, β₂, γ₂. Then: α₁ + β₁ + γ₁ = 180º α₂ + β₂ + γ₂ = 180º Since the two angles are congruent α₁ = α₂ = α β₁ = β₂ = β α + β + γ₁ = 180º α + β + γ₂ = 180º γ₁ = 180º – (α + β) γ₂ = 180º – (α + β) Therefore γ₁ = γ₂
5 answers · Mathematics · 8 years ago
• ### What is 2.47% of 3092 and what is the formula to figure it out?

2.47 % of 3092 = 2.47 × 3092 / 100 = 76.3724
2.47 % of 3092 = 2.47 × 3092 / 100 = 76.3724
4 answers · Mathematics · 8 years ago
• ### Find the area of the triangle determined by the points P(-5,4,-5), Q(-5,-4,6) and R(3,-3,4)?

a = PQ = √{[(–5) – (–5)]² + [(–4) – (+ 4)]² + [(6) – (–5)]²} ............ = √{[0]² + [–8]² + [11]²} ............ = √(0 + 64 + 121) ............ = √185 b = QR = √{[(3) – (–5)]² + [(–3) – (–4)]² + [(4) – (6)]²} ............ = √[8² + (+1)² + (–2)²] ............ = √(64 + 1 + 4) ............ = √69 c = RP = √{[(–5) – (3)]² + [(4) – (–3)]² +... show more
a = PQ = √{[(–5) – (–5)]² + [(–4) – (+ 4)]² + [(6) – (–5)]²} ............ = √{[0]² + [–8]² + [11]²} ............ = √(0 + 64 + 121) ............ = √185 b = QR = √{[(3) – (–5)]² + [(–3) – (–4)]² + [(4) – (6)]²} ............ = √[8² + (+1)² + (–2)²] ............ = √(64 + 1 + 4) ............ = √69 c = RP = √{[(–5) – (3)]² + [(4) – (–3)]² + [(–5) – (4)]²} ............ = √[(–8)² + (7)² + (–9)²] ............ = √[64 + 49 + 81] ............ = √194 Because the length of the sides are in surds, we will compute in decimal and use Heron's formula A = √[s(s – a)(s – b)(s – c)] where s = (a + b + c)/2 a = √185 = 13.60147 b = √69 = 8.30662 c = √194 = 13.92839 s = (13.60147 + 8.30662 + 3.92839)/2 = 17.91824 s – a = 17.91824 – 13.60147 = 4.31677 s – b = 17.91824 – 8.30662 = 9.61162 s – a = 17.91824 – 13.92839 = 3.98985 A = √[17.91824(4.31677)(9.61162)(3.98985) A = 54.4633
3 answers · Mathematics · 8 years ago
• ### Whats the decimal of this 8 bit twos complement number?

10111011₂ reverse the bits 01000100 add 1 to the last bit 01000101₂ = 1 × 2⁶ + 1 × 2² + 1 × 2⁰ = 64 + 4 + 1 = 69 Therefore 10111011₂ = –69
10111011₂ reverse the bits 01000100 add 1 to the last bit 01000101₂ = 1 × 2⁶ + 1 × 2² + 1 × 2⁰ = 64 + 4 + 1 = 69 Therefore 10111011₂ = –69
1 answer · Mathematics · 8 years ago
• ### Which two numbers multiply to make -3 and add to make 6?

xy = -3 x + y = 6 y = 6 - x x(6 - x) = -3 6x - x² = - 3 0 = x² - 6x - 3 (Cannot be factored with rational coefficients) Problem could not be solved with real answers.
xy = -3 x + y = 6 y = 6 - x x(6 - x) = -3 6x - x² = - 3 0 = x² - 6x - 3 (Cannot be factored with rational coefficients) Problem could not be solved with real answers.
4 answers · Mathematics · 8 years ago
• ### How do I write this polynomial in factored form? x^3+7x^2+10x ?

x³ + 7x² + 10x = x(x² + 7x + 10) = x(x + 2)(x + 5)
x³ + 7x² + 10x = x(x² + 7x + 10) = x(x + 2)(x + 5)
4 answers · Mathematics · 8 years ago